Human hepatitis E virus circulation in Bulgaria: Deep Bayesian phylogenetic analysis for viral spread control in the country. Issue 1 (24th September 2018) - Cella, Eleonora; Golkocheva‐Markova, Elitsa; Sagnelli, Caterina; Scolamacchia, Vittoria; Bruni, Roberto; Villano, Umbertina; Ciccaglione, Anna Rita; Equestre, Michele; Sagnelli, Evangelista; Angeletti, Silvia; Ciccozzi, Massimo
Abstract : Hepatitis E virus (HEV) infection in Bulgaria is endemic, as demonstrated by the seroprevalence of antibody against the virus in the general population and by the high prevalence of clinical cases registered. In this study, a deep Bayesian phylogenetic analysis has been performed to provide information on the genetic diversity and the spread of HEV genotypes in Bulgaria. Three different data sets of HEV virus was built for genotyping by the maximum likelihood method, for evolutionary rate estimated by Bayesian Markov Chain Monte Carlo approach, for demographic history investigation and for selective pressure analysis. The evolutionary rate for genotype 3e, was 351 × 10 −3 substitution/site/year (95% highest posterior density [95% HPD]: 145 × 10 −3 ‐575 × 10 −3 ). The root of the time to the most recent common ancestor of the Bayesian maximum clade credibility tree of HEV 3e genotype corresponded to 1965 (HPD 95% 1949‐1994). The Bulgarian sequences mainly clustered in the main clade (clade A). The monophyletic clade included all Bulgarian genotype 3e sequences. The demographic history showed a slight growth from 1995 to 2000, followed by a sort of bottleneck in 2010s, a peak in 2011 and a new growth to 2015. Selection pressure analysis did not show sites under positive pressure but 64 statistically significant sites under negative selection. Molecular epidemiological surveillance by Bayesian phylogeny of HEV virus can contribute to trace the way of human infection after contact with swine source directly or heating meat improving public health control.